A perspective on metabolic surgery from a gastroenterologist - Yu-Fong Syu; Akio Inui; Chih-Yen Chen (Elsevier, 2017)
Type 2 diabetes (T2D) and obesity are important public health problems. The global prevalence of diabetes mellitus is 8.8%. Interventional diabetology and obesitology have been recently advocated as treatment options for T2D and obesity. The roles of metabolic surgery such as Roux-en-Y gastric bypass, sleeve gastrectomy, gastric banding, and biliopancreatic diversion are focused. Different types of metabolic surgeries have different glucose-lowering and weight loss effects. Endoscopic treatments include the intra-gastric balloon (to restrict the gastric volume) and duodenal-jejunal bypass liner (DJBL, as a malabsorptive procedure). Anatomic changes in the gastrointestinal tract may cause alterations in gut hormones, bile acids, adipokines, inflammatory cytokines, hepatokines, myokines, gut microbiota, and even unidentified factors. Modulating gut hormones, including foregut (ghrelin, glucose-dependent insulinotropic polypeptide) and hindgut (glucagon-like peptide-1, peptide YY) hormones, through metabolic surgeries improves glycemic homeostasis. Metabolic surgeries reduce pro-inflammatory cytokines and increase anti-inflammatory cytokines. Metabolic surgeries also regulate one's appetite through the new establishment of jejunal nutrient sensing. Therefore, the effects of metabolic surgery and DJBL implantation emphasize the crucial role of the small intestine in glucose homeostasis. Removing diabetogenic or obesogenic factors from the duodenum and/or jejunum may help to solve the problems of diabetes and obesity in the future.